Three-dimensional displacement field of the 2010 Mw 8.8 Maule earthquake from GPS and InSAR data with the improved ESISTEM-VCE method - Xiong, Luyun; Xu, Caijun; Liu, Yang; Zhao, Yingwen; Geng, Jianghui; Ortega-Culaciati, Francisco (Frontiers in Earth Science, 2022)
The 2010 Mw 8.8 Maule earthquake occurred offshore central Chile and ruptured ∼500 km along the megathrust fault resulting from the oceanic Nazca plate subducting beneath the continental South American plate. The Maule earthquake produced remnant crustal displacements captured by a vast set of geodetic observations. However, given the nature of the observational techniques, it is challenging to extract its accurate three-dimensional coseismic deformation field with high spatial resolution. In this study, we modified the extended simultaneous and integrated strain tensor estimation from geodetic and satellite deformation measurements (ESISTEM) method with variance component estimation algorithm (ESISTEM-VCE) to retrieve the three-dimensional surface displacement field of this event by integrating the interferometric synthetic aperture radar (InSAR) and global positioning system (GPS) measurements. The ESISTEM-VCE method accounts for the spatial correlation of surface displacement among the adjacent points and determine the accurate weight ratios for different data sets, but also uses the uncertainties of GPS data and considers the different spatial scales from the different datasets. In the simulation experiments, the RMSEs of the ESISTEM-VCE method are smaller than those of the ESISTEM and ESISTEM-VCE (same d0) methods, and the improvements of 97.1%, 3.9%, and 84% are achieved in the east-west, north-south, and vertical components, respectively. Then, we apply the proposed methodology to the 2010 Mw 8.8 Maule earthquake, to obtain a three-dimensional displacement field that could provide fine deformation information. In the east-west component, the significant deformation is in the north of the epicenter, closed to the Constitución, with a maximum westward displacement of 495.5 cm. The displacement in the north-south component is relatively small compared to that in the east-west component. The maximum uplift reaches 211.8 cm, located at the southwest of the Concepción. Finally, the derived vertical displacements are also compared with field investigations, indicating that the ESISTEM-VCE method can obtain more accurate weight of different datasets and perform better than the ESISTEM method. The results highlight that the earthquake ruptured along the NE-SW direction, with a dominant thrust and a relatively small component of right-lateral strike-slip, coinciding with the characteristics of subduction and right-lateral shear. The experiments with the simulated and real data suggest that the improved ESISTEM-VCE method in this study is feasible and effective.